2008
DOI: 10.1007/s11104-008-9690-5
|View full text |Cite
|
Sign up to set email alerts
|

Early events in the life of apple roots: variation in root growth rate is linked to mycorrhizal and nonmycorrhizal fungal colonization

Abstract: Early events of mycorrhizal and nonmycorrhizal fungal colonization in newly-emerging roots of mature apple (Malus domestica Borkh) trees were characterized to determine the relationship of these events to fine root growth rate and development. New roots were traced on root windows to measure growth and then collected and stained to quantify microscopically the presence of mycorrhizal and nonmycorrhizal fungal structures. Most new roots were colonized by either mycorrhizal or nonmycorrhizal fungi but none less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 46 publications
1
33
0
Order By: Relevance
“…Through the dramatic influence to surrounding soil, root pathogens could not only affect root growth, but also could affect the levels of phytochemicals in plants (Resendes et al 2008;Nogales et al 2009;Bais et al 2005). In our results, three ginsenosides, Rb 1 , Re and Rg 1 in ginseng roots, were influenced differently by soilborne pathogens F. solani and F. oxysporum-mediated infection.…”
Section: Discussionmentioning
confidence: 56%
“…Through the dramatic influence to surrounding soil, root pathogens could not only affect root growth, but also could affect the levels of phytochemicals in plants (Resendes et al 2008;Nogales et al 2009;Bais et al 2005). In our results, three ginsenosides, Rb 1 , Re and Rg 1 in ginseng roots, were influenced differently by soilborne pathogens F. solani and F. oxysporum-mediated infection.…”
Section: Discussionmentioning
confidence: 56%
“…There is a sizable portion of fine roots that remains relatively inactive even from the first days of birth. Other age related studies, such as those on P uptake and respiration (Bouma et al 2001), root browning (Comas et al 2000, N uptake and respiration , and fungal infection rate (Resendes et al 2008) found similar variation in root function within fine roots of the same age, where a large proportion of the roots appears to be inactive.…”
Section: Root Age and Nitrate Uptakementioning
confidence: 76%
“…However, many absorptive roots, especially in woody plants, only extend 2 or 3 cm in the first days of life and then stop growing (e.g. Resendes et al 2008). These short,very fine lateral roots age, but we have a limited understanding of their nutrient uptake physiology as they age (Lucash et al 2007), particularly in light of the fact the tip ceases growing (using an ordering scheme where roots with no laterals are 1st order) (Fitter 1982).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used fresh roots to compare with leaf litter in our decomposition analysis because there is no evidence that roots senesce, abscise, and are shed discretely the way that leaves do and are. Rather, roots gradually lose function as they age (Eissenstat and Volder 2004) and are colonized by saprotrophic fungi while still living (Resendes et al 2008). Therefore, the difference between a live root and a decomposing root represents a continuum, making it impossible to collect dead roots that have not already begun to decompose or for which the stage of decomposition can be controlled.…”
Section: Methodsmentioning
confidence: 99%